2012
DOI: 10.1038/bjc.2012.387
|View full text |Cite
|
Sign up to set email alerts
|

Whole sentinel lymph node analysis by a molecular assay predicts axillary node status in breast cancer

Abstract: Background:The one-step nucleic acid amplification (OSNA) assay is a rapid procedure for the detection of lymph node (LN) metastases using molecular biological techniques. The aim of this study was to assess the reliability of the whole sentinel lymph node (SLN) analysis by the OSNA assay as a predictor of non-SLN metastases.Methods:Consecutive 742 patients with breast cancer were enroled in the study. The association of non-SLN or ⩾4 LN metastases with clinicopathological variables was investigated using mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 25 publications
1
26
0
2
Order By: Relevance
“…This is a limitation of such studies, yet there is no way of avoiding it. It would be interesting to perform OSNA examination on the whole lymph node, as is done in breast cancer [45,46]. Unfortunately, since no studies evaluating the accuracy of OSNA in thyroid cancer have been carried out, it is impossible, from an ethical and legal point of view, to perform OSNA instead of histopathology.…”
Section: Prace Oryginalnementioning
confidence: 99%
“…This is a limitation of such studies, yet there is no way of avoiding it. It would be interesting to perform OSNA examination on the whole lymph node, as is done in breast cancer [45,46]. Unfortunately, since no studies evaluating the accuracy of OSNA in thyroid cancer have been carried out, it is impossible, from an ethical and legal point of view, to perform OSNA instead of histopathology.…”
Section: Prace Oryginalnementioning
confidence: 99%
“…Ohi et al (2012) and Osako et al (2013) demonstrated that the NSLN macrometastatic rate increased in proportion to CK19 mRNA copy numbers [7,8]; Ohi et al verified that the CK19 mRNA copy number in SLN is the most important predictive factor of NSLN metastases, and that higher copy numbers are strongly associated with four or more axillary lymph node metastases [7].…”
Section: Introductionmentioning
confidence: 99%
“…OSNA, validada como la técnica de elección para el diagnóstico intraoperatorio del GC 30,31 , ha dado lugar al concepto de CTT, definida como la suma del número de copias de cada uno de los GC del paciente y que ha sido considerada por algunos investigadores como la variable independiente con mayor poder predictivo de afectación de los ganglios axilares no centinela 18,19 , y más exacta, precisa y reproducible que la medida histológica sobre el corte de tejido. Nuestro objetivo es caracterizar el valor del PM y la CTT, mediante su inclusión en distintos modelos predictivos, para predecir el estado ganglionar del resto de la axila tras la biopsia de GC.…”
Section: Discussionunclassified
“…Se define la CTT como la suma del número de copias de ARNm de la citoqueratina 19 (ARNm-CK-19) de todos los GC y ha sido identificada por algunos autores como el factor independiente predictivo de metástasis en los ganglios axilares no centinela de mayor potencia 18,19 .…”
Section: Introductionunclassified